Faktor - Faktor Penyebab Penumpukan Antrean Pendaftaran Pasien Rawat Jalan Di Rumah Sakit Maranatha - Nursipa Nursipa; Desy Widyaningrum (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Queue buildup at outpatient registration is an issue that can affect the quality of hospital services. Long queues have the potential to increase patient waiting times, reduce satisfaction, and hinder service effectiveness. This study aims to analyze the factors causing queue buildup during outpatient registration at Maranatha Hospital. The study employs a descriptive approach utilizing observation, interviews, and document review. Research informants include registration staff and relevant personnel from the medical records unit. Data were analyzed descriptively to identify the causes of queue buildup based on aspects of human resources, work methods, facilities and infrastructure, and service systems. The findings are expected to provide insight into the factors contributing to queue buildup, thereby serving as a basis for the hospital to evaluate and improve the effectiveness of outpatient registration services.